Re-shaping Presentation of Financial Statements – IASB's Exposure Draft on General Presentation and Disclosure. - Sarmah, Porag (International Journal of Psychosocial Rehabilitation, 2020)
Clear and precise presentation of accounting items and its appropriate disclosures are the prerequisites for meaningful interpretation of the financial statements. The International Accounting Standard Board (IASB) has initiated different projects to enhance transparency and improve the understandability of the financial statements in the current decade. It has initiated a mega project, namely 'Basic communication of Financial Reporting' recently, some part of the project has already been completed, and some are in progress. On 17 December 2019, it has published an exposure draft 'General presentation and Disclosure' as a part of the project to streamline certain aspects of primary financial statements, particularly statement of profit and loss. The exposure draft proposes to introduce a new definition subtotals with respect to operating profit and some other definition of aggregation and disaggregation. It has also proposed to introduce management performance measures as a non-GAAP requirement in the presentation of financial statements and its annexed notes. It is expected that when the exposure draft is being finalized, some deficiencies in the presentation of financial statements may be removed that justified for better understanding, transparency, and comparability from the part of the investors and analysts.The paper attempts to present an overview of the proposed exposure draft on 'General presentation and disclosure' along with a critical discussion. Further, it also aims to highlight the current directives of IAS-1 and its shortcomings. Moreover, the paper tries to analyze the implications of the proposed exposure draft on Indian companies.